THE INFLUENCE OF PROFITABILITY, LEVERAGE AND COMPANY SIZE ON TAX AVOIDANCE - Suliana, Suliana; Suhono, Suhono (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This study aims to determine the effect of profitability, leverage and firm size on tax avoidance in automotive sub-sector manufacturing companies and components listed on the IDX. In this study using quantitative descriptive methods. The type of data in this research is secondary data. The data collection technique used was purposive sampling. The analysis method used is multiple linear regression analysis. The results showed that profitability had no effect on tax avoidance. Meanwhile, leverage and firm size have a significant positive effect on tax avoidance.